DISTRIBUTION OF INTESTINAL HELMINTHOSIS IN SHEEP IN DAGESTAN - V. M. Shamhalov; O. A. Magomedov; M. V. Shamhalov; N. H. Gulahmedova; R. M. Bakrieva (Российский паразитологический журнал)
Distribution of intestinal helminthosis in sheep in plain and foothill areas of Dagestan has been studied. Materials and methods  By the method of helminthological post mortem examination of intestinal tract a high infection rate of cestodes and nematodes in sheep was determined.  Results and discussion  The infection of young sheep up to 14 months of age with Moniezia spp. was 68,7 %, Thysaniezia giardi - 12,5 % at intensity of infection 6,7±0,7 expl./head; 2,7±0,3; 2,0±0,3; 106,9±6,7 and 68,3±7,3 expl./head respectively. In addition, a mono-infection was observed in 53,1 % of sheep, 12,5 % - were infected with two types of helminths, 9,4 % - with three, 9,4 % with four helminth types. The infestation of sheep more than two years of age was: with Moniezia spp. 17,9 %, Th. giardia - 12,8, A. centripunctata - 10,2, Nematodirus spp. -17,9 and Bunostomum spp. - 12,8 % at II (intensity of infection) 5,3±0,5 expl./head; 5,4±0,6; 4,2±0,4; 171,8±9,3 and 67,2±6,8 expl./ head respectively. The mono-infection was found in 23,0 % of sheep , in 15,4 % - the infestation with two helminth types, in 2,5 % - with three and in 2,5 % – with four helminth types. At mixed infection the intensity of infection with particular helminth types decreases in comparison with the mono infection. The pathogenic effect of helminths increases at infestation with several helminth types.